2015
DOI: 10.1515/cclm-2014-0633
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial interleukin-6 in the setting of left ventricular mechanical assistance: relation with outcome and C-reactive protein

Abstract: Cardiac IL-6 levels do not contribute to improve risk profile of LVAD recipients in relation to clinical inpatient post-implantation. Instead, plasma IL-6 and serum CRP concentrations are more effective in predicting the severity of the clinical course in the early phase of LVAD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…So, patients receiving a centrifugal flow cfLVAD were operated on earlier in their disease process, preventing a stage with sliding on inotropes or even worse. Moreover, it was reported that preoperative IL-6 and CRP levels were higher in INTERMACS I patients scheduled for cfLVAD implantation, suggesting that patients with end-stage heart failure classified in a lower class of INTERMACS score (e.g., INTERMACS I or II) probably have a more pronounced disbalance in inflammatory biomarkers preoperatively with a probable worse outcome, such as vasoplegia and related early post-cfLVAD implantation complications, such as right ventricular failure and kidney failure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, patients receiving a centrifugal flow cfLVAD were operated on earlier in their disease process, preventing a stage with sliding on inotropes or even worse. Moreover, it was reported that preoperative IL-6 and CRP levels were higher in INTERMACS I patients scheduled for cfLVAD implantation, suggesting that patients with end-stage heart failure classified in a lower class of INTERMACS score (e.g., INTERMACS I or II) probably have a more pronounced disbalance in inflammatory biomarkers preoperatively with a probable worse outcome, such as vasoplegia and related early post-cfLVAD implantation complications, such as right ventricular failure and kidney failure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%